2020
DOI: 10.4081/fe.2020.415
|View full text |Cite
|
Sign up to set email alerts
|

Spiders from Molise (Italy): state of knowledge, new faunistic data and taxonomic notes (Arachnida: Araneae)

Alessio Trotta

Abstract: The spiderfauna of Molise includes 98 species belonging to 64 genera and 21 families; 48 species are firstly reported for this region, 19 are earlier record confirmed and 31 are earlier record to be confirmed. The following new combination and new synonymies are proposed: Zelotes caprearum (Pavesi, 1875) = Zelotes caporiaccoi Denis, 1953 (not Zelotes caporiaccoi Roewer, 1951) syn. n. = Zelotes denapes Platnick, 1993 syn. n.; Cozyptila nigristernum (Dalmas, 1922) comb. n. = Cozyptila thaleri Marusik and Kovblyu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This species, described from France ( Mazzia and Cornic 2020 ) and recently found in Italy for the first time ( Trotta 2024 ), was collected in agricultural patches that are common in the Appia Antica Regional Park. On the whole, six Italian endemic species were found in the study area: Dysdera romana , known exclusively from lowland and hillside localities near the Tyrrhenian coast of central and south Latium and from Emilia-Romagna ( Gasparo and Di Franco 2008 , Lami et al 2023 ); the recently-described Centromerus tongiorgii , which was already found in Latium at Canale Monterano ( Ballarin and Pantini 2020 ), but which is also present in Abruzzo, Basilicata, Marche, Umbria, Emilia-Romagna, Liguria, Lombardy and Veneto ( Ballarin and Pantini 2020 , Nardi and Marini 2021 ); Cybaeodes marinae a nocturnal spider found in Thyrrenian areas of Latium, Sardinia, Calabria, Sicily, Liguria and Tuscany ( Di Franco 1989 , Pantini and Mazzoleni 2018 , Picchi 2020 , Caria et al 2021 , Trotta 2023 ); Harpactea sardoa found in south Sardinia and Latium ( Alicata 1966 , Brignoli 1979a ); Pseudeuophrys perdifumo , only known from a few sites in Calabria and Campania ( Van Helsdingen 2015 ); Nemesia bosmansi , recently described by Decae (2024) from sandy dunes of the Parco Nationale del Circeo (Latium). It is also important to mention some species with limited distribution like Araeoncus longisculus and Syedra nigrotibialis , which can be found only in mainland Italy, Sardinia and Corsica ( Simon 1926 , Müller 1986 , Pantini and Isaia 2019 ); Dysdera lantosquensis , which has an Alpino-Appenninic distribution and is mainly distributed in central and northern Italy and on the French border ( Řezáč et al 2018 ); Dysdera bottaziae , an Appennino-Dinaric sub-endemic species found in southern Italy, Croatia and Bosnia and Herzegovina (…”
Section: Discussionmentioning
confidence: 99%
“…This species, described from France ( Mazzia and Cornic 2020 ) and recently found in Italy for the first time ( Trotta 2024 ), was collected in agricultural patches that are common in the Appia Antica Regional Park. On the whole, six Italian endemic species were found in the study area: Dysdera romana , known exclusively from lowland and hillside localities near the Tyrrhenian coast of central and south Latium and from Emilia-Romagna ( Gasparo and Di Franco 2008 , Lami et al 2023 ); the recently-described Centromerus tongiorgii , which was already found in Latium at Canale Monterano ( Ballarin and Pantini 2020 ), but which is also present in Abruzzo, Basilicata, Marche, Umbria, Emilia-Romagna, Liguria, Lombardy and Veneto ( Ballarin and Pantini 2020 , Nardi and Marini 2021 ); Cybaeodes marinae a nocturnal spider found in Thyrrenian areas of Latium, Sardinia, Calabria, Sicily, Liguria and Tuscany ( Di Franco 1989 , Pantini and Mazzoleni 2018 , Picchi 2020 , Caria et al 2021 , Trotta 2023 ); Harpactea sardoa found in south Sardinia and Latium ( Alicata 1966 , Brignoli 1979a ); Pseudeuophrys perdifumo , only known from a few sites in Calabria and Campania ( Van Helsdingen 2015 ); Nemesia bosmansi , recently described by Decae (2024) from sandy dunes of the Parco Nationale del Circeo (Latium). It is also important to mention some species with limited distribution like Araeoncus longisculus and Syedra nigrotibialis , which can be found only in mainland Italy, Sardinia and Corsica ( Simon 1926 , Müller 1986 , Pantini and Isaia 2019 ); Dysdera lantosquensis , which has an Alpino-Appenninic distribution and is mainly distributed in central and northern Italy and on the French border ( Řezáč et al 2018 ); Dysdera bottaziae , an Appennino-Dinaric sub-endemic species found in southern Italy, Croatia and Bosnia and Herzegovina (…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in a lower number of species recorded in southern regions, despite the great habitat and climatic diversity that characterizes peninsular Italy. Recent faunistic works focusing on spiders in southern regions show how easily new regional and national records can originate from these areas (Ijland et al 2012, Ijland and van Helsdingen 2019, Pantini et al 2020, Trotta 2020, Dentici et al 2022. Given that other species in the same family and even in the same genus show a similar distribution pattern to that observed for H. graecum, and that this species is not known to exhibit synanthropic habits, it is unlikely that the observed population in Italy is the result of a human-mediated introduction.…”
Section: Methodsmentioning
confidence: 99%